Kegiatan Skrining Intensitas Gatal pada Populasi Lanjut Usia di Panti Lansia St. Anna - Ruslim, Welly Hartono; Firmansyah, Yohanes; Moniaga, Catharina Sagita; Mashadi, Fladys Jashinta; Gunaidi, Farell Christian; Gracieene Gracienne; Nathaniel, Fernando (Jurnal Suara Pengabdian 45, 2024)
Pruritus, or itching, is a common symptom in seniors that has a significant impact on their quality of life. Primary skin disorders such as xerosis, atopic dermatitis, and scabies, as well as systemic diseases such as cancer, chronic renal failure, cholestasis, hyperthyroidism, diabetes mellitus, iron deficiency anemia, and certain medications, can cause this condition. Chronic pruritus, which is common in individuals over 60 years of age, can cause discomfort, sleep disturbances, and psychological stress. This activity uses the PDCA (Plan-Do-Check-Act) methodology to screen for pruritus intensity in the elderly in St. Anna. One individual (2.4%) reported mild pruritus, while 12 individuals (29.3%) reported severe pruritus. Routine assessment using the 12-PSS provides important information for managing pruritus in the elderly, meeting clinical and research needs, and improving patient care and quality of life.